Experimental study on optimization of the initial support structure of super-large section highway tunnel. Issue 5 (October 2021) - Chen, H B; Jiang, Y J; Han, W; Sun, H B; Li, N B; Chen, Y Q; Lu, W; Luan, Y C
Abstract: To improve the economic benefits, on the premise of ensuring the bearing capacity of the initial support, the optimized research on the initial support structure of the super-large section highway tunnel was carried out. Based on the first single-hole four-lane highway tunnel with the largest excavation section in Shandong Province, this paper puts forward a support scheme of optimizing the arch spacing for the initial support and sets up the comparative field test to study the differences between the original scheme and the optimized scheme in bearing mechanical properties and controlling tunnel stability. The tunnel deformation characteristics, surrounding rock pressure release law and arch stress distribution rule of the two support schemes were obtained by monitoring the displacement and stress of different monitoring sections. The results show that compared with the original scheme, the clearance convergence of the optimized scheme is increased by 3.65%, the settlement increased by 5.69%, the surrounding rock pressure increased by 18.34%, and the arch stress decreased by 11.18%. In addition, the maximum stress of the arch is only 49.6% of the yield strength of steel. Both the original scheme and the optimized scheme have enough strength reserve to resist the deformation of surrounding rock and ensure the stability of the tunnel in a short time. This study can provide engineering references for constructing a super-large section highway tunnel under the same condition.